.........................................

Algebra
Tutor: None Selected Time limit: 1 Day

Apr 26th, 2015

(x + 8)(x + 5) = x(x + 5) + 8(x + 5) = x^2 + 5x + 8x + 40 = x^ 2 +13x +40

(x - 9)(x + 3) = x(x + 3) - 9(x + 3) = x^2 + 3x - 9x - 27 = x^2 - 6x - 27

(x - 10)(x + 2) = x(x + 2) - 10(x + 2) = x^2 + 2x - 10x - 20 = x^2 - 8x - 20

(x + 11)(x + 3) = x(x + 3) + 11(x + 3) = x^2 + 3x + 11x + 33 = x^2 + 14x + 33 

Apr 27th, 2015

Did you know? You can earn $20 for every friend you invite to Studypool!
Click here to
Refer a Friend
...
Apr 26th, 2015
...
Apr 26th, 2015
Dec 7th, 2016
check_circle
Mark as Final Answer
check_circle
Unmark as Final Answer
check_circle
Final Answer

Secure Information

Content will be erased after question is completed.

check_circle
Final Answer